A book - Gerstein, Mordicai (New York : Roaring Brook Press, 2009)
A young girl living in a book tries to find a story of her own while figuring out what a reader is and thinking about the stories of her family members.
Cover title.
Booklist starred.
School Library Journal starred.
Wilson's Children.
2.8
K-3
Keywords: Books -- Juvenile fiction; Characters and characteristics in literature -- Juvenile fiction; Families -- Juvenile fiction; Books -- Fiction; Characters in literature -- Fiction; Family life -- Fiction; Books -- Fiction; Characters and characteristics in literature -- Fiction; Family life -- Fiction